2002
DOI: 10.1046/j.1469-0705.2002.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

First‐trimester trisomy screening: nuchal translucency measurement training and quality assurance to correct and unify technique

Abstract: Global qualitative review of images from one sonographer may be preferable to assessment of individual aspects of images. Results from global qualitative review correspond well with findings from quantitative analysis, indicating that the latter can be applied for ongoing audit. Observation of divergent results should prompt extensive personal feedback, rather than a written report, to prevent sonographers from settling in their own, inappropriate technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
121
0
24

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(148 citation statements)
references
References 10 publications
3
121
0
24
Order By: Relevance
“…For example, should the quality score be high if all criteria but caliper placement were to be met, even though the result might be poor? 7 These systems have been found too cumbersome to be used for routine quality assessment. They might be of more value during the initial training period, or when quantitative assessment indicates the need for further scrutiny.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, should the quality score be high if all criteria but caliper placement were to be met, even though the result might be poor? 7 These systems have been found too cumbersome to be used for routine quality assessment. They might be of more value during the initial training period, or when quantitative assessment indicates the need for further scrutiny.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Acquiring the skill to properly measure NT requires specialized training and oversight. 7 Recognizing this, several national and international programs have been established to train and qualify sonographers, and also to assess their ability to consistently and accurately quantify the NT thickness. 8 -11 The hands-on performance training is usually evaluated through still images submitted to one, or a panel of, expert sonographers.…”
mentioning
confidence: 99%
“…The fetal medicine foundation has established a process of training and quality assurance for the appropriate introduction of NT screening into clinical practice, 1,2 and several studies have demonstrated that an ongoing regular audit of images and the distribution of measurements of NT are essential for the assessment of the quality of a center. [24][25][26][27] A similar process of training, certification and quality assurance oriented to fetal medicine units in DV flow can be suggested after our experience.…”
Section: Discussionmentioning
confidence: 99%
“…Die vorgeburtliche Risikoabklärung insgesamt sowie jede einzelne ihrer Komponenten (Ultraschall, laboratoriumsmedizinische Untersuchungen, Algorithmus) müssen einer kontinuierlichen Qualitätssicherung unterzogen werden. Durch eine kontinuierliche Qualitätssicherung kann das Problem der Unterschätzung der Nackentransparenz deutlich verringert und so die Entdeckungsrate erhöht werden [17,18,19]. Eine externe Qualitätssicherung ist insbesondere für den Bereich Ultraschall wesentlich, weil es sich bei der fetalen Nackentransparenz um eine Messung im Bereich um 0,1 mm handelt und deren Genauigkeit direkt von der Qualifikation des Anwenders abhängt [17].…”
Section: Begründungunclassified
“…Durch eine kontinuierliche Qualitätssicherung kann das Problem der Unterschätzung der Nackentransparenz deutlich verringert und so die Entdeckungsrate erhöht werden [17,18,19]. Eine externe Qualitätssicherung ist insbesondere für den Bereich Ultraschall wesentlich, weil es sich bei der fetalen Nackentransparenz um eine Messung im Bereich um 0,1 mm handelt und deren Genauigkeit direkt von der Qualifikation des Anwenders abhängt [17]. Eine regelmäßige jährliche Überprüfung der Messergebnisse und der Ultraschallbilder dient dem Absichern präziser Ergebnisse.…”
Section: Begründungunclassified